2010
DOI: 10.1590/s1808-18512010000100014
|View full text |Cite
|
Sign up to set email alerts
|

Approach-related morbidity in transthoracic anterior spine surgery: a clinical study and review of literature

Abstract: BACKGROUND: Anterior access to the thoracic spine is done by open thoracotomy (OTC) or video-assisted thoracoscopic surgery (VATS). VATS is known as the method which results in lower morbidity rates, but there is little evidence of its less invasiveness. Objective: The current study yielded for outcome data concerning patients' perception of approach-related morbidity (ArM) following OTC for spinal surgery and that of a control group having a chest tube thoracotomy (CTT). METHODS: We performed a questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
1
1
0
Order By: Relevance
“…This was most likely related to the fact that the amount of correction needed to achieve target kyphosis varied in each patient. Notably, similar to another study on adolescent idiopathic scoliosis undergoing anterior open transthoracic correction [48], average ArM was low (19 %). However, age had a significant correlation with ArM.…”
Section: Discussionsupporting
confidence: 83%
“…This was most likely related to the fact that the amount of correction needed to achieve target kyphosis varied in each patient. Notably, similar to another study on adolescent idiopathic scoliosis undergoing anterior open transthoracic correction [48], average ArM was low (19 %). However, age had a significant correlation with ArM.…”
Section: Discussionsupporting
confidence: 83%
“…This suggests that tumors growing anteriorly might not be detected until they have grown large enough to affect the lateral or posterior tracts responsible for pain or sensory changes. In our series, ventral IM tumors were located between T9 and T12, making it difficult to consider an anterior approach 33) . As with other studies, poor clinical outcomes observed in our study were likely to be influenced by these factors.…”
Section: Discussionmentioning
confidence: 80%